(untitled) (Praxis Educativa, 2012)
Although Brazil is a country predominantly agrarian, in the rural zone of Brazil there is a not a schooling system effectively from the rural zone. The lack of that space of formal education is not the main cause of country poverty but it is one more factor that reinforces it. Until 1891 such education was not mentioned in constitutional texts revealing the national government negligence. The developed practices in those schools seem not to give importance to the association between life and formal educational activities. The possibility of the existence of a country school associated to the rural reality grows up with the pedagogical model of alternance that emerged as an attempting to fulfill the formal education demand in the country. The alternance pedagogy, on its libertarian, progressive and consciousness dimension, dialogues to FREIRE’s principles: defending the education as a continuous process of cultural construction and community development to self-supporting. This paper aims at collaborate with an educational propose in the country, which is also to the country, from the rural zone of Jaguaquara, once the researching place is the Escola Rural Taylor-Egídio (ERTE), in Jaguaquara district.